Systemic approach to families bringing up disabled child - Jusienė, Roma (Psichologija, 1999)
Birth of a handicapped child is usually viewed as a common family crisis. Parents of a handicapped child are considered to deal with grief and adaptation to child's disability reactions, and chronic stress later on. Valuable insights considering the psychological problems of the families with handicapped child may be derived from the systems theory. The present article deals briefly with the main concepts of the family with disabled child as a system. Also several causes of dysfunctional family system are analysed.
Keywords: family; disabled child; systemic approach